Method for preparing 69mpa resistant proppant using high baria oil-based cuttings dry residue and proppant

CN123003258APending Publication Date: 2026-10-30SICHUAN JUNHE ENVIRONMENTAL PROTECTION
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611218422.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-12
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0006]本发明提供利用高钡油基岩屑干渣制备抗69MPa支撑剂的方法及支撑剂,解决了高钡油基岩屑干渣在制备抗69MPa支撑剂中因烧结粘连、粘壁问题而导致产量和产率低的技术问题,提高了高钡油基岩屑干渣制备的抗69MPa支撑剂颗粒的产量和产率,提高和拓宽了高钡油基岩屑干渣的综合利用

Benefits of technology

1、本发明在干生球烧结过程中喷洒防粘连剂,能及时吸附表面出现的微量SiO2熔融液相,避免球体间因表面液相析出发生互相粘连和粘壁,提高了抗69MPa筒体强度的支撑剂产率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003258A_ABST
    Figure CN123003258A_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of proppant for oil and gas field, and particularly relates to a method for preparing 69MPa-resistant proppant by using high-barium oil-based rock debris dry slag and the proppant. The method comprises the steps of dry green ball powder spraying sintering, kiln cooling and polishing to obtain 69MPa-resistant proppant; wherein the temperature of the high-temperature sintering section of the rotary kiln is 1110-1130℃; wherein the residence time of the dry green ball in the high-temperature sintering section is 80-125min, and the total residence time of the dry green ball in the rotary kiln is >5h; during the temperature rising process of powder spraying sintering, a 200-320 mesh anti-adhesion agent is sprayed into the rotary kiln; the anti-adhesion agent is 0.5-3.0wt.% of the mass of the dry green ball. The present application solves the technical problem of low yield due to sintering adhesion in the preparation of 69MPa-resistant proppant by using high-barium oil-based rock debris dry slag, improves the sintering yield and yield of 69MPa-resistant proppant, and improves and broadens the comprehensive utilization of rock debris solid waste.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of proppants for oil and gas fields, specifically relating to a method and proppant for preparing a 69MPa-resistant proppant using high-barium oil-based dry rock cuttings. Background Technology

[0002] Oil-based rock cuttings, or dried slag, are the residual solid phases from the treatment of drilling sludge in oil, natural gas, or shale gas wells. Classified as general solid waste, their extremely complex composition limits their reuse value. Currently, reuse is limited to raw materials for sintered bricks and cement production, or for road hardening at drilling platforms. With the gradual shrinking of the building materials industry and the upgrading and transformation of the construction market, the market for sintered bricks is continuously narrowing. Due to the complex composition of oil-based rock cuttings, their use as cement raw materials is extremely difficult. Furthermore, with the saturation of the real estate market, cement demand has decreased sharply, rendering the disposal of this slag in the building materials sector practically nonexistent. To promote the healthy and circular development of the oil and gas extraction industry, an increasing number of inventors and academic researchers believe that reusing this slag deep underground is a new development direction. Although many studies have utilized oil-based rock cuttings to prepare petroleum fracturing proppant, the limitations on the composition of the dried slag and the difficulty in implementing multi-stage isothermal sintering processes hinder industrial production.

[0003] Currently, sampling and analysis of oil-based rock cuttings from different regions and well sites have revealed that their main components are CaO, SiO2, Al2O3, Fe2O3, and BaSO4, with some K2O, Na2O, MgO, organic residues, and other trace metal elements. Compositional analysis of the dry residue obtained during continuous oil-based rock cuttings processing shows the following fluctuation ranges for each component: CaO: 8.01–22.3%, SiO2: 16.04–39.21%, Al2O3: 2.14–9.61%, and BaSO4: 15.44–56.67%. BaSO4 primarily originates from its role as a weighting agent, mixing with rock cuttings minerals to form high-barium oil-based rock cuttings. Traditional processes primarily involve pretreatment calcination, crushing, granulation, and sintering to prepare proppant. However, the following problems commonly exist in the traditional proppant preparation process based on this high-barium oil-based rock cuttings: 1. The issue of BaSO4 content fluctuation and matching with sintering conditions: Since the BaSO4 content in oil-based rock cuttings fluctuates by more than 40% and has a high melting point, this fluctuation will affect the actual sintering melting point of the green pellets, severely impacting the temperature design in the sintering process and also affecting the breakage rate of the 40-70 mesh cylinders with a strength of 69 MPa. 2. Industry standards have specific requirements for the particle size distribution of proppant and the breakage rate of the cylinder strength, such as particle size distributions of 40-70 mesh and 70-140 mesh. Due to the difference in the particle size of the green balls, uneven heating during sintering in the rotary kiln leads to over-burning / adhesion of small-diameter green balls and under-burning of large-diameter green balls. Consequently, the breakage rate is greater than 9wt.% under the cylinder strength of 69MPa, which is unqualified.

[0004] 3. In the sintering study of the dry green balls supported by the high barium oil-based rock cuttings dry slag at 1110-1130℃, the actual yield of the 69MPa-resistant proppant prepared by the high barium oil-based rock cuttings dry slag was 36.84% due to the occurrence of ball sticking and wall sticking in the rotary kiln.

[0005] Therefore, improving the yield of high-barium oil-based rock cuttings in the preparation of 69MPa-resistant proppant remains a very important technical challenge. Summary of the Invention

[0006] This invention provides a method and a proppant for preparing 69MPa-resistant proppant using high-barium oil-based rock cuttings, solving the technical problem of low yield and output caused by sintering adhesion and wall sticking in the preparation of 69MPa-resistant proppant from high-barium oil-based rock cuttings. This invention improves the yield and output of 69MPa-resistant proppant particles prepared from high-barium oil-based rock cuttings, and enhances and broadens the comprehensive utilization of high-barium oil-based rock cuttings.

[0007] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is as follows: A method for preparing a 69MPa-resistant proppant using high-barium oil-based rock cuttings includes the steps of pre-treating and calcining, pre-grinding and homogenizing, batching, grinding and homogenizing, granulating and drying oil-based rock cuttings with a BaSO4 content of 15.44 to 56.67 wt.%, and preparing them into dry green balls. The method also includes the steps of spraying powder and sintering dry green pellets in a rotary kiln, cooling and polishing them after exiting the kiln, and obtaining a 69MPa-resistant support agent; wherein the temperature of the high-temperature sintering section of the rotary kiln is 1110~1130℃; wherein the residence time of the dry green pellets in the high-temperature sintering section is 80~125min, and the total residence time of the dry green pellets in the rotary kiln is >5h; During the heating process of the powder spraying sintering, an anti-blocking agent with a particle size of 200-320 mesh is sprayed into the rotary kiln; the amount of the anti-blocking agent is 0.5-3.0 wt. of the mass of the dry green pellets.

[0008] Preferably, in the method of the present invention, the anti-blocking agent is any one or any combination of CaO powder, Al2O3 powder, magnesium oxide powder, zircon powder, mullite powder and zirconium oxide powder.

[0009] Preferably, in the method of the present invention, the anti-blocking agent is CaO powder or Al2O3 powder.

[0010] Preferably, in the method of the present invention, the anti-blocking agent is CaO powder, which is inexpensive.

[0011] Preferably, in the method of the present invention, the heating rate of the powder spraying sintering is <1.0℃ / min.

[0012] Preferably, in the method of the present invention, the anti-blocking agent is sprayed into the rotary kiln when the temperature is raised to 400-600°C, and the spraying is completed when the temperature is raised to 900-1000°C.

[0013] Preferably, in the method of the present invention, the method further includes: after pre-grinding and homogenization and before grinding and homogenization, adding auxiliary materials to form a mixture; wherein the auxiliary materials contain CaO, SiO2 and / or Al2O3.

[0014] Preferably, in the method of the present invention, the pre-ground powder in the mixture is >75 wt.%.

[0015] More preferably, in the method of the present invention, the BaO content a wt.%, CaO content b wt.%, SiO2 content c wt.%, and Al2O3 content d wt.% in the mixture satisfy the following requirements i and ii: i: Calculate the SiO2 content c1 wt.% (equimolar with CaO, based on CaO content b wt.%); q, where c1 <c,b+c1>20 wt.%; ii: Calculate the BaO content a1 wt.%, which is equimolar with Al2O3, and the SiO2 content c2 wt.%, which is twice the molar with Al2O3, based on the Al2O3 content d wt.%; where 0 <a-a1<20 wt.%,4 wt.%<c-c1-c2<6 wt.%;d+a1+c2>25wt.%;60 wt.%<b+c1+c2+d+a1 Preferably, in the method of the present invention, the particle size of the pre-milled homogenized material is 200-320 mesh, and the residue on an 80µm water sieve is <10wt.%.

[0016] Preferably, in the method of the present invention, the D97 after grinding and homogenization is 14-16 μm.

[0017] Preferably, in the method of the present invention, the particle size distribution of the dried green pellets covers 40-70 mesh; the breakage rate of the dried green pellets at a cylinder compressive strength of 1 MPa is ≤1 wt.%.

[0018] Preferably, in the method of the present invention, the cooling is performed at an average cooling rate of 3 to 8 °C / min to 600 °C, followed by air cooling to room temperature.

[0019] The above method was used to prepare a 69MPa-resistant proppant.

[0020] The beneficial effects of this invention are: 1. In the process of dry green ball sintering, the present invention sprays an anti-blocking agent, which can adsorb the trace amount of SiO2 molten liquid phase that appears on the surface in time, and avoids the balls from sticking to each other and sticking to the wall due to the precipitation of surface liquid phase, thereby improving the proppant yield with resistance to 69MPa cylinder strength.

[0021] 2. The present invention sprays an anti-blocking agent during the dry green ball sintering process, which can effectively reduce the adhesion between proppant particles, effectively reduce the impact of proppant product particle adhesion on the cylinder breakage rate, and reduce the breakage rate of proppant at 69MPa cylinder strength.

[0022] 3. Based on pretreatment calcination, pre-grinding and homogenization, batching, grinding and homogenization, granulation and drying, heating and sintering and cooling, this invention can prepare a 69MPa-resistant proppant, and solid waste resources are effectively utilized. Attached Figure Description

[0023] Figure 1 Photograph of the proppant product in Example 1 of this invention; Figure 2 Photograph of the proppant product in Comparative Example 5 of this invention; Figure 3 Photograph of the proppant product of Comparative Example 7 of this invention. Detailed Implementation

[0024] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be described in detail below. Obviously, the described embodiments are merely some embodiments of this invention, and not all embodiments. Based on the embodiments of this invention, all other implementation methods obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0025] A method for preparing a 69MPa-resistant proppant using high-barium oil-based rock cuttings includes the steps of pre-treating and calcining, pre-grinding and homogenizing, batching, grinding and homogenizing, granulating and drying oil-based rock cuttings with a BaSO4 content of 15.44 to 56.67 wt.%, and preparing them into dry green balls. The method also includes the steps of spraying powder and sintering dry green pellets in a rotary kiln, cooling and polishing them after exiting the kiln, and obtaining a 69MPa-resistant support agent; wherein the temperature of the high-temperature sintering section of the rotary kiln is 1110~1130℃; wherein the residence time of the dry green pellets in the high-temperature sintering section is 80~125min, and the total residence time of the dry green pellets in the rotary kiln is >5h; During the heating process of the powder spraying sintering, an anti-blocking agent with a particle size of 200-320 mesh is sprayed into the rotary kiln; the amount of the anti-blocking agent is 0.5-3.0 wt. of the mass of the dry green pellets.

[0026] In some instances, the anti-blocking agent is any one or more of CaO powder, Al2O3 powder, magnesium oxide powder, zircon powder, mullite powder, and zirconium oxide powder.

[0027] In some instances, the anti-blocking agent is CaO powder or Al2O3 powder.

[0028] In some instances, the anti-adhesion agent is CaO powder.

[0029] In some instances, the heating rate of the powder spraying sintering is <1.0℃ / min.

[0030] In some cases, the anti-blocking agent is sprayed into the rotary kiln when the temperature reaches 400-600°C, and the spraying is completed when the temperature reaches 900-1000°C.

[0031] In some instances, the method further includes the step of adding auxiliary materials to form a mixture after pre-grinding and before grinding and homogenization; wherein the auxiliary materials contain CaO, SiO2 and / or Al2O3.

[0032] Preferably, in the method of the present invention, the BaO content a wt.%, CaO content b wt.%, SiO2 content c wt.%, and Al2O3 content d wt.% in the mixture satisfy the following requirements i and ii: i: Calculate the SiO2 content c1 wt.% (equimolar with CaO, based on CaO content b wt.%); q, where c1 <c,b+c1>20 wt.%; ii: Calculate the BaO content a1 wt.%, which is equimolar with Al2O3, and the SiO2 content c2 wt.%, which is twice the molar with Al2O3, based on the Al2O3 content d wt.%; where 0 <a-a1<20 wt.%,4 wt.%<c-c1-c2<6 wt.%;d+a1+c2>25wt.%;60 wt.%<b+c1+c2+d+a1。

[0033] In some instances, the pre-milled and homogenized particle size is 200-320 mesh, and the residue on an 80µm water sieve is <10wt.%.

[0034] In some instances, the D97 after grinding and homogenization was 14–16 μm.

[0035] In some instances, the dry green pellets have a particle size distribution covering 40-70 mesh; the breakage rate of the dry green pellets at a cylinder compressive strength of 1 MPa is ≤1 wt.%.

[0036] In some instances, the cooling process involves cooling to 600°C at an average rate of 3–8°C / min, followed by air cooling to room temperature.

[0037] Preferably, pretreatment calcination creates sufficient conditions for the subsequent firing of the proppant to form barium feldspar at lower temperatures and pressures. Simultaneously, it prevents the accumulation of SO3 generated during barium sulfate decomposition during proppant sintering, which can trap micropores within the proppant and reduce strength. Simultaneously, it removes CO2 from the carbonates, preventing surface cracking of the spheres caused by carbonate decomposition during high-temperature calcination of the proppant. This process also removes residual organic matter, some mineral crystal water, and volatile or easily liquidated substances such as Cl-, K+, and Na+ from the dry slag, as well as the hydrophobic oil film formed on the surface of the dry slag in the previous treatment process. This prevents gas escape and cracking or micropores from the proppant surface before sufficient sintering strength is achieved, which could lead to glass leakage during high-temperature sintering and cause problems such as ball adhesion and kiln wall adhesion. Simultaneously, during the pre-sintering stage, low-melting-point oxides such as potassium and sodium can be removed in advance (after being mixed with powder and sintered into blocks, they are sieved out). This prevents a significant decrease in the minimum eutectic temperature of the reacting minerals during later proppant sintering, avoiding premature liquidation and problems such as ball adhesion and kiln wall adhesion. Therefore, high-barium oil-based rock debris dry slag undergoes pre-treatment calcination at 1050-1100℃ before pre-grinding, homogenization, and batching.

[0038] In some instances, pre-grinding and homogenization includes: pre-grinding the pretreated dry residue using a closed-circuit ball mill system with a classifier, controlling the particle size to within 200-320 mesh, and ensuring that the residue on an 80µm water sieve is less than 10%. The ground dry residue is then homogenized, requiring that any sample taken for analysis after homogenization shows a deviation of no more than 1% for the same components.

[0039] In some cases, samples of the pre-milled and homogenized powder are taken and quantitatively analyzed for the contents of CaO, SiO2, Al2O3, and BaO. Then, pre-auxiliary materials are batched. The principle of batching is to add appropriate amounts of one or more auxiliary materials containing CaO, SiO2, and Al2O3. The auxiliary materials must not contain minerals that are prone to decomposition reactions and gas release during high-temperature sintering, such as chemical water of crystallization, carbonates, and sulfates. Extensive data demonstrates that to produce a qualified 69MPa sample, the total amount of theoretically generated barium feldspar (BaAl2Si2O8) and wollastonite (CaSiO3) after batching should be greater than 60 wt.%, the BaO content in the remaining minerals should be less than 20%, and the remaining SiO2 content should be controlled between 4-6%.

[0040] In some instances, the auxiliary materials and pre-milled homogenized dry residue are uniformly mixed according to the proportion of the ingredients using a weighing scale and then fed into a ball mill for grinding. The particle size D97 of the ground powder is 14-16 μm.

[0041] In some instances, the powder after grinding the ingredients is fully homogenized, and the fluctuation of the same chemical composition after homogenization does not exceed 0.5 wt.%.

[0042] In some instances, powders with the same chemical composition fluctuation not exceeding 0.5% after homogenization are pelletized using a pelletizing machine. The pellet size is 40-70 mesh, and the sphericity is not less than 0.9. After pelletizing, the moisture is slowly dried, and the breakage rate under 1MPa cylinder pressure does not exceed 1%. This ensures that the green pellets have sufficient surface strength to maintain the pellets from cracking during the sintering heating process, thereby providing sufficient pressure for the chemical reaction of the internal minerals.

[0043] In some instances, industrial rotary kilns are used to sinter green pellets, with natural gas used as the raw material for roasting. During sintering, the maximum heating rate of the rotary kiln is less than 1℃ / min, the temperature of the high-temperature sintering section inside the kiln is controlled between 1110-1130℃, the residence time in the high-temperature zone is 80-120min, and the total residence time of the material in the kiln is not less than 5h.

[0044] In some cases, to avoid the adverse effects of green pellets sticking to the walls due to prolonged residence in the high-temperature zone, a specially structured burner is used. A trace amount of CaO powder is continuously added to the primary air of the burner and sprayed onto the pellets. This promptly adsorbs the trace amounts of molten SiO2 on the surface, preventing the pellets from sticking together and adhering to the walls due to surface liquid phase precipitation. After exiting the kiln, the proppant undergoes slow cooling and heat preservation to ensure that the internal crystals continue to grow at high temperatures, while the surface vitrified body slowly shrinks, gradually eliminating internal stress. Once the slowly cooled proppant has cooled to below 600℃, it can be naturally cooled to room temperature in a single-cylinder cooler using ventilation, avoiding rapid cooling that could cause microcracks and reduce strength.

[0045] In some instances, the cooled proppant is surface-ground and polished to remove CaO particles adhering to the surface of the particles. Then, it is sieved to the appropriate particle size, ultrasonically washed, and dried to obtain a proppant resistant to 69 MPa. Preferably, an abrasive flow polisher is used for polishing, with spherical silicon carbide as the abrasive. Polishing is divided into two steps: (1) Coarse polishing: 80-120 mesh spherical silicon carbide is used for coarse polishing, with the proportion of spherical silicon carbide being 30-45% of the proppant, to quickly remove white particles; (2) Fine planing: 400-600 mesh spherical silicon carbide is used for fine planing, with the proportion of spherical silicon carbide being 20-30% of the proppant, to improve surface smoothness. The time for coarse polishing and fine planing is 1-5 minutes, which can be shortened or extended according to the polishing effect.

[0046] In some cases, sampling and analysis of dried slag after processing oil-based cuttings from different regions and well sites revealed that its main components were CaO, SiO2, Al2O3, and BaSO4, with some K2O, Na2O, MgO, Fe2O3, organic residues, and other trace metal elements. Compositional analysis of dried slag obtained during continuous oil-based cuttings processing showed the following fluctuation ranges for each component: CaO: 8.01-22.3%, SiO2: 16.04-39.21%, Al2O3: 2.14-9.61%, BaSO4: 15.44-56.67%.

[0047] Experimental analysis revealed that the sintered proppant particles mainly contained four phases: wollastonite (CaSiO3), barium feldspar (BaAl2Si2O8), barium sulfate (BaSO4), and silicon dioxide (SiO2). Based on this, it is inferred that under suitable temperature and pressure conditions during high-temperature sintering, the above mineral assemblage can generate two new minerals with high strength: wollastonite and barium feldspar. The reaction equations are as follows: (1) ; (2) or ; Wollastonite (CaSiO3) readily forms needle-like or fibrous crystals during sintering, effectively preventing crack propagation and serving as the primary load-bearing framework in the proppant. Barium feldspar (BaAl2Si2O8) possesses an extremely low coefficient of thermal expansion and excellent chemical stability, making it an ideal high-strength phase in ceramic proppants and a reinforcing phase. Silica (SiO2) is a glassy phase; an appropriate glassy phase can promote sintering, fill gaps between grains, bind different phases, and increase overall strength. However, excessive glassiness can lead to increased brittleness and lower strength in the proppant, while also causing it to easily adhere to each other. Barium sulfate (BaSO4) has a much lower hardness and strength than silicate crystals. If barium sulfate cannot be completely converted to barium feldspar during high-temperature sintering, the residual barium sulfate can easily cause a porous structure, reducing the proppant's strength. During sintering, low-melting-point minerals form a glassy body to fill the gaps, while high-melting-point minerals, acting as fillers, are encapsulated or bonded into a whole by the glassy body or newly formed mineral crystals, thus achieving high compressive strength.

[0048] Based on the above principles, by precisely controlling the formation ratio of wollastonite, barium feldspar, and vitreous under suitable temperature and pressure conditions, it is theoretically possible to manufacture proppant products of varying strengths from the aforementioned mixture. This invention patent, based on the above mechanism, utilizes existing industrial equipment to mass-produce 69MPa oil fracturing proppant.

[0049] To further demonstrate the effectiveness of the ingredients of this invention in improving the adhesion of green pellets during sintering, the following examples and comparative examples are provided: In the following examples and comparative examples, the main chemical composition of the pre-ground homogenized materials obtained after calcining and pre-grinding of high-barium oil-based rock debris with different chemical compositions at 1080℃ is shown in Table 1 below.

[0050] Table 1

[0051] In the following examples and comparative examples, the main components of kaolin are: SiO2: 55.79 wt.%, Al2O3: 36.63 wt.%.

[0052] The main component of bauxite is Al2O3: 75.09 wt.%.

[0053] The main component of yellow sandstone is SiO2: 94.04%.

[0054] The main components of bentonite are SiO2: 57.10% and Al2O3: 13.04%.

[0055] CaO powder purity ≥ 90.0 wt.%, particle size 200-320 mesh.

[0056] The following examples and comparative examples show the statistical results of the pre-ground powder and auxiliary material mass ratios and the theoretical values ​​calculated after batching, as well as the results of the calculation. Table 2 shows the results of the calculation.

[0057] Table 2

[0058] Example 1 This embodiment provides a method for preparing a 69MPa-resistant proppant using high-barium oil-based dry rock cuttings, including the following steps: 1. Ingredients: According to the mass ratio shown in Table 2, take the pre-ground powder and the auxiliary materials and mix them to obtain the mixture; 2. Fine grinding and homogenization: The mixture is finely ground to obtain finely ground powder with D97=14.3μm; the finely ground powder is homogenized to obtain finely homogenized powder with the same component deviation <0.5 wt.%; 3. Granulation and drying: The fine and homogenized powder is granulated and dried to obtain dry green balls with a particle size of 40-70 mesh, a sphericity of 0.9, and a breakage rate of 0.69 wt.% at 1 MPa cylinder strength; 4. Heating and sintering: The dry green pellets are placed in a rotary kiln. The flue gas from the kiln tail is 500℃±10℃. After 3.5 hours, it enters the high-temperature sintering section, where the temperature is 1120±10℃, and stays in this high-temperature zone for 100 minutes. The dry green pellets stay in the rotary kiln for a total of 5.2 hours. During the heating process, 1.2wt.% of CaO powder by weight of the dry green pellets is sprayed into the rotary kiln. 5. Cooling: After exiting the kiln, the temperature is reduced from 1120℃ to 600℃ at a rate of 4.5℃ / min; then, natural ventilation is used to cool it to room temperature in a single-cylinder cooler. 6. Polishing: Polish the proppant cooled to room temperature and remove the CaO powder generated during polishing to obtain a 40-70 mesh proppant.

[0059] A photograph of the proppant product in this embodiment is attached. Figure 1 As shown.

[0060] Example 2

[0061] In this embodiment, the pre-ground powder and the auxiliary materials were mixed according to the mass ratio shown in Table 2 to obtain a mixture; and a 40-70 mesh support was prepared according to steps 2-6 of Example 1.

[0062] Example 3

[0063] In this embodiment, the pre-ground powder and the auxiliary materials were mixed according to the mass ratio shown in Table 2 to obtain a mixture; and a 40-70 mesh support was prepared according to steps 2-6 of Example 1.

[0064] Comparative Example 1 This comparative example was prepared according to the mass ratios shown in Table 2 and steps 2-6 of Example 1 to obtain a 40-70 mesh support.

[0065] Comparative Example 2 This comparative example was prepared according to the mass ratios shown in Table 2 and steps 2-6 of Example 1 to obtain a 40-70 mesh support.

[0066] Comparative Example 3 This comparative example was prepared according to the mass ratios shown in Table 2 and steps 2-6 of Example 1 to obtain a 40-70 mesh support.

[0067] Comparative Example 4 The difference between this comparative example and Example 1 is that the residence time of the green pellets in the high-temperature sintering section is 60 min; the total sintering residence time is 4 h; and the remaining steps are the same as in Example 1.

[0068] Comparative Example 5 The difference between this comparative example and Example 1 is that CaO powder was not sprayed during the sintering heating process, while the remaining steps were the same as in Example 1.

[0069] A photograph of the proppant product prepared in this comparative example is attached. Figure 2 As shown.

[0070] Comparative Example 6 The difference between this comparative example and Example 1 is that after sintering and exiting the kiln, it was directly air-cooled to room temperature.

[0071] Comparative Example 7 The difference between this comparative example and Example 1 is that the proppant cooled to room temperature was not polished.

[0072] The product photo of this comparative proportion propeptide is as follows: Figure 3 As shown.

[0073] Performance testing The sphericity and breakage rate of the proppant in Examples 1-5 and Comparative Examples 1-5 at a cylinder strength of 69 MPa were tested based on the test methods in SY / T5108.

[0074] The statistical results of the proppant sphericity and breakage rate of the cylinder with a strength of 69 MPa in Examples 1-5 and Comparative Examples 1-5 are shown in Table 3.

[0075] Table 3

[0076] According to Table 3 and the appendix Figure 1-3As can be seen, the proppant products of Examples 1-5 have full particles and no cracks on the surface; Comparative Example 5 did not spray CaO powder during the heating and sintering process, the sintering yield was 36.84%, and the breakage rate under the 69MPa cylinder strength was not up to standard (the standard requires a breakage rate of <9wt.%).

[0077] Comparative Example 2 was not properly formulated, resulting in substandard strength and an unqualified product.

[0078] Although the ingredients were mixed in Comparative Example 3, the total theoretical amount of barium feldspar and wollastonite was insufficient after mixing, and the remaining SiO2 content was higher than 6%, resulting in the proppant product strength not meeting the standard and the product being unqualified.

[0079] In Comparative Example 4, the remaining SiO2 content after mixing was less than 4%, and the strength of the proppant product did not meet the standard, making the product unqualified.

[0080] Comparative Example 6 showed that the cooling rate was too fast in the early stage of cooling, resulting in the proppant product strength not meeting the standard and the product being unqualified.

[0081] In Comparative Example 7, the acid solubility of CaO powder on the surface of the unpolished proppant particles was significantly increased. Due to the presence of CaO powder on the particle surface, under a cylinder strength of 69 MPa, the CaO powder on the proppant particle surface squeezed the particles, causing the proppant particles to be easily broken.

[0082] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a 69MPa-resistant proppant using high-barium oil-based rock cuttings, comprising the steps of pre-treating and calcining, pre-grinding and homogenizing, batching, grinding and homogenizing, granulating and drying oil-based rock cuttings with a BaSO4 content of 15.44–56.67 wt.%, and preparing dry green balls; Its features are, The method further includes the steps of spraying powder and sintering dry green pellets in a rotary kiln, cooling and polishing them after exiting the kiln, and obtaining a 69MPa-resistant support agent; wherein, the temperature of the high-temperature sintering section of the rotary kiln is 1110~1130℃; wherein, the residence time of the dry green pellets in the high-temperature sintering section is 80~125min, and the total residence time of the dry green pellets in the rotary kiln is >5h; During the heating process of the powder spraying sintering, an anti-blocking agent with a particle size of 200-320 mesh is sprayed into the rotary kiln; the amount of the anti-blocking agent is 0.5-3.0 wt. of the mass of the dry green pellets.

2. The method according to claim 1, characterized in that: The anti-blocking agent is any one or more of CaO powder, Al2O3 powder, magnesium oxide powder, zircon powder, mullite powder, and zirconium oxide powder; preferably, the anti-blocking agent is CaO powder or Al2O3 powder; more preferably, the anti-blocking agent is CaO powder.

3. The method according to claim 1, characterized in that: The heating rate of the powder spraying sintering is <1.0℃ / min.

4. The method according to claim 1, characterized in that: When the dry green pellets are heated to 400-600℃, an anti-blocking agent is sprayed into the rotary kiln, and the spraying is completed before the green pellets are heated to 900-1000℃.

5. The method according to claim 1, characterized in that, The method further includes: after pre-grinding and homogenization, and before grinding and homogenization, adding auxiliary materials and pre-grinding powder to form a mixture; wherein the auxiliary materials contain CaO, SiO2 and / or Al2O3; preferably, the pre-grinding powder in the mixture is >75 wt.%; more preferably, the BaO content awt.%, CaO content b wt.%, SiO2 content c wt.%, and Al2O3 content d wt.% in the mixture meet the following requirements i and ii: i: Calculate the SiO2 content c1 wt.% (equimolar with CaO, based on CaO content b wt.%); q, where c1 <c,b+c1>20wt.%; ii: Calculate the BaO content a1 wt.%, which is equimolar with Al2O3, and the SiO2 content c2 wt.%, which is twice the molar with Al2O3, based on the Al2O3 content d wt.%; where 0 <a-a1<20 wt.%,4 wt.%<c-c1-c2<6 wt.%;d+a1+c2>25 wt.%;60wt.%<b+c1+c2+d+a1。 6. The method according to claim 1, characterized in that: The pre-milled and homogenized particle size is 200-320 mesh, and the residue on an 80µm water sieve is <10wt.%.

7. The method according to claim 1, characterized in that: After grinding and homogenization, the D97 value is 14–16 μm.

8. The method according to claim 1, characterized in that: The dry green pellets have a particle size distribution of 40-70 mesh; the breakage rate of the dry green pellets under 1 MPa cylinder pressure is ≤1 wt.%.

9. The method according to claim 1, characterized in that: The cooling process involves cooling the temperature to 600°C at an average rate of 3–8°C / min, followed by air cooling to room temperature.

10. The 69MPa-resistant proppant prepared by the method according to any one of claims 1-9.